Sto lat polskiego przemysłu samochodów osobowych - Leśniak-Moczuk, Arkadiusz D. (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
Stuletni okres historii przemysłu motoryzacyjnego w Polsce można podzielić na trzy fazy. Pierwsze polskie konstrukcje samochodów osobowych sięgające początku XX wieku nie zostają wdrożone do produkcji. W okresie międzywojennym zakup licencji zagranicznych zapoczątkowuje rozwój przemysłu motoryzacyjnego. W Polsce Ludowej konstrukcje samochodowe polskich inżynierów trafiające do seryjnej produkcji i kontynuacja produkcji opartej na licencjach zagranicznych wpływają na wzrost dynamiki podaży samochodów osobowych, znajdujących nabywców na rynku krajowym i w eksporcie. Transformacja systemowa otwiera rynki krajów zachodnich dla nabywców samochodów osobowych oraz pozwala na przepływ kapitału obcego uruchamiającego montownie marek zagranicznych w Polsce w miejsce rodzimego przemysłu motoryzacyjnego.

One can divide the one- hundred- year period of Polish automotive industry history into three phases. The first passenger cars designed in Poland in the beginning of the XXth century were not implemented into a serial or mass production. Some overseas car licenses were purchased and started automotive industry development in the interwar period. In the PRL time some designs of Polish engineers came into serial production. The cars used to be accompanied by cars manufactured under overseas manufacturer’s licenses. The cars influenced passenger car supply dynamism. Those cars used to be sold on domestic and overseas markets. The system transformation has made it possible for Polish customers to purchase cars on western markets. Thanks to the overseas money, accompanied by oversees licenses, car assembly facilities were built in place of Polish cars.
Keywords: polski przemysł motoryzacyjny; samochody osobowe; produkcja i montaż samochodów; Polish automotive industry; passenger cars; manufacturing and car assembly